Illocutionary Acts by Kamala Harris in the 2020 Vice Presidential Debate - Ni Kadek Tarisa; I Gusti Ayu Vina Widiadnya Putri (RETORIKA: Jurnal Ilmu Bahasa, 2026)
Abstract. An illocutionary act plays a significant role in political discourse, as it reveals the speaker’s intentions and persuasive strategies through language. While previous studies have explored illocutionary acts in social media and advertisement, this study focuses on the formal political debate setting, which remain unexplored. This study examines the types of illocutionary acts and their functions in the 2020 United States Vice Presidential Candidate Debate between Senator Kamala Harris and Vice President Mike Pence. This study focuses solely on the utterances delivered by Kamala Harris. A qualitative descriptive method was employed, analyzing Kamala Harris’s utterance using Searle (1976) classification to identify the types of illocutionary acts. Based on the results of this study, there are 65 data of illocutionary acts, which can be divided into 33 (51%) assertive acts, 12 (18%) directive acts, 10 (15%) commissive acts, and 10 (15%) expressive acts. This study also found various functions of each act based on the theory of  Yule (1996). Assertive acts include functions such as reporting, informing, and asserting; directive acts involve requesting and advising; commissive acts include refusing, promising, and vowing; and expressive acts feature praising, thanking, and condoling. The most frequently used function is reporting, with 9 occurrences (14%), which indicates Kamala Harris’s emphasis on presenting factual arguments. The findings highlight how language in political debates is used strategically to establish credibility, convey ideology, and persuade audiences.